The Age of Screens: Investigating the Influence of Screen Media on the Language Choice and Identity Construction of Primary Grade Learners - Bucayon – Simbajon, Darlyn Fegi (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to explore the impact of mobile screen media on the language choice and identity construction of primary-grade learners. A descriptive research design was used, and five primary-grade students aged 6-11 from Iligan City were interviewed. One-on-one interviews were conducted to gather data. Findings indicate that the language profile of the participants included a mix of English, Tagalog, and Bisaya languages, with English being the primary language used at school and home. Factors influencing language choice included the languages spoken by those around them, the prestige of English, and exposure to media and gadgets. Screen media exposure positively and negatively affected children's self-perception: it enhanced their understanding of different cultures and sense of worth. It fostered cross-cultural identities and made some feel estranged from their families and peers. The findings underscore the importance of recognizing the quality and nature of interactions between children and screen media.